It's hard to do fashion in Istanbul ‐ or is it?. Issue 1 (1st March 2019) - Ulusoy, Nilay
All major cities have a unique 'atmosphere' that influences inhabitants and visitors, and that shapes ideas and objects related to it. The identity of a city is a social construct, and this symbolic, imaginary construct is associated with a specific local production system. With its heritage combining Roman, Byzantine and Ottoman elements and its contemporary urban life, Istanbul is recognized as one of the world's cultural capitals. Turkey, on the other hand, is one of the world's leading textile-manufacturing countries, with the majority of products made in and around Istanbul. This is noteworthy at a time when the consumer fashion industry simultaneously is drawing on discourses of exoticism, the primitive, orientalism and authenticity, one factor underlying the breakdown of the monopoly of Milan, Paris, New York and London on fashion. Drawing on primary research undertaken through semi-structured interviews with designers, social media specialists and textile engineers in Turkey, this article provides an overview of the contemporary Turkish fashion industry with a focus on neo-Ottoman style. The article begins by evaluating Istanbul's contemporary fashion industry and continues with how fashion produced in Istanbul affects Istanbul's image worldwide, and finally explains how Istanbul reciprocally affects the designs created in this city.